1996
DOI: 10.1021/ma960468f
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Fluorescent Naphthol-Based Polymers

Abstract: A fluorescent polymer of 2-naphthol is prepared using the oxidative enzyme horseradish peroxidase encapsulated in the microstructured system of AOT/isooctane reversed micelles. The monomer, being amphiphilic, partitions to the oil−water interface with the hydroxyl moieties directed toward the microaqueous core. The enzyme is encapsulated in the water core. The precipitated polymer of naphthol has the morphology of single and interconnected microspheres and is soluble in a range of polar and nonpolar organic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 26 publications
6
68
1
Order By: Relevance
“…The polymer showed activity at the air-water interface unlike the corresponding monomer, with aggregates under identical conditions. Premachandran et al [63] reported the enzymatic synthesis of fluorescent naphtholbased polymers. In recent years, fluorescent polymers have attracted considerable attention because of their applications in plastic scintillators [64], luminescent solar concentrators [65], high laser-resistant materials [66], laser dyes [67], and fiber optic sensors [68].…”
Section: Kobayashi Etmentioning
confidence: 99%
“…The polymer showed activity at the air-water interface unlike the corresponding monomer, with aggregates under identical conditions. Premachandran et al [63] reported the enzymatic synthesis of fluorescent naphtholbased polymers. In recent years, fluorescent polymers have attracted considerable attention because of their applications in plastic scintillators [64], luminescent solar concentrators [65], high laser-resistant materials [66], laser dyes [67], and fiber optic sensors [68].…”
Section: Kobayashi Etmentioning
confidence: 99%
“…Efforts were focused to improve the electrooptical properties of polyphenols with longer conjugated segments. Premachandran et al [7] reported the synthesis of naphthol-based polymers to increase the conjugation lengths in the backbone. The polyphenols with longer conjugation lengths in polymer main chain and pendent groups have also been reported by Kayak et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of phenols and anilines with hydrogen peroxide catalyzed by different oxidoreductases is an alternative ecofriendly route to synthesize the industrially important polyaromatics. [9][10][11][12][13][14][15][16] Similarly the vinylic monomers have also been polymerized with hydrogen peroxide catalyzed by HRP and related enzymes under milder conditions with high yields. The formation of polymer 2 was indicated in the absence of a peak at 1612 cm -1 for olefinic stretching and a carbonyl absorption from 1672 to 1655 cm -1 in its IR spectra.…”
Section: Introductionmentioning
confidence: 99%